The IoV Meets Open RAN: An O-RAN-based IoV Architecture (ELEKTRIKA- Journal of Electrical Engineering, 2024)
The race towards a better-connected world has led to innovations in network connectivity and the embedding of intelligence into various types of devices. Intelligent devices require an intelligent network infrastructure and design in order to reach their maximum potential. Recently, the concept of Open Radio Access Networks (Open RAN, O-RAN) has gained a lot of attention with the formation of the O-RAN Alliance which seeks to usher in the next phase of cellular network interoperability, intelligence and design. Another key concept that has emerged in recent years is the Internet of Vehicles (IoV) which has been described as a driver for next generation Intelligent Transportation Systems (ITS). This paper proposes an architecture that brings together these two concepts and explores how the design principles of the O-RAN can be incorporated into the IoV by using a bottom-up approach. It also discusses the benefits of an O-RAN-based IoV, some perceived challenges with its implementation and the way forward.
Keywords: Intelligent transportation systems; internet of vehicles; O-RAN; Open RAN